A-202 Cognitive Predictors of Verbal Memory Test Performance in an Outpatient Clinical Sample. (17th August 2022) - Smith, Cassandra; Daniel, Michael; Michael, Paul
Abstract: Objective: Investigate the influence of non-memory cognitive abilities on auditory-verbal memory test performance in a clinical sample. Method: Archival data were analyzed for 129 patients [53.5% female; mean (SD): age = 46.48 (13.95), education = 13.82 (2.75)] who completed neuropsychological evaluation at a neurology/neuropsychology clinic. Five separate hierarchical regression analyses were conducted with these dependent variables: the California Verbal Learning Test-II (CVLT-II) Total Recall, Short-Delay Free Recall, and Long-Delay Free Recall, Logical Memory (LM) I and II subtests of the Wechsler Memory Scale, 4th edition (WMS-IV); independent variables were the same for each analysis and included neuropsychological tests of attention/working memory, visual-spatial/construction, language, and executive functions. Results: Delis-Kaplan Executive Function System Trails Switching accounted for 31-39% of the variance in the Total and Free Recall trials of the CVLT-II (p < .001). Wechsler Adult Intelligence Scale, Fourth Edition Vocabulary subtest accounted for 28 and 29% of the variance in LM I and LM II (p < .001). Conclusions: While language ability accounts for most of the variance in narrative verbal memory test performance, executive functions related to set shifting and processing speed account for most of the variance in word list learning. When interpreting below average scores on these verbal memory tests, it is important to consider the differential impact of non-memory cognitive abilities related to the memory test format.